Peran Teknologi Blockchain dalam Keamanan dalam Privasi Data - Putri Rizkia Wardhani; Muhammad Irwan Padli Nasution (Universitas Muhammadiyah Enrekang, 2023)
In the increasingly advanced digital era, data security and privacy are important and challenging issues. In this context, blockchain technology emerges as a promising solution. This research aims to explore the role of blockchain technology in enhancing data security and privacy. Through a comprehensive literature review, we gathered information about the key features in blockchain technology that are relevant to data security and privacy. Our research results show that blockchain can provide significant advantages in terms of transparency, reliability, data integrity, and data owner control. Apart from that, blockchain technology has also enabled the adoption of decentralized digital identities, which provide a higher level of privacy for users. Although there are challenges that need to be overcome, such as scalability and operational costs, this research concludes that blockchain technology has great potential in protecting data from attacks and privacy breaches. To optimize the role of blockchain technology in the context of data security and privacy, collaboration between academia, industry and other interested parties is required, as well as advanced research to overcome challenges and maximize the benefits of this technology.